Considerable Variation of Antibacterial Activity of Cu Nanoparticles Suspensions Depending on the Storage Time, Dispersive Medium, and Particle Sizes; BioMed Research International; Vol. 2015 - Zakharova O. V. Olga Vladimirovna; Godymchuk (Godimchuk) A. Yu. Anna Yuryevna; Gusev A. A. Aleksandr Anatoljevich; Gulchenko S. I. Svyatoslav Igorevich; Vasyukova I. A. Inna Anatoljevna; Kuznetsov Denis Valerjevich D. V. Denis Valerjevich (2015, 2015)
Title screen